Effect of Next Generation Fertilizers on Growth and Yield Potential of Maize (Zea mays L.) - M. A. A. Faroque; Alok Kumar Paul; Asaduzzaman; Parimal Bissus; M. S. Islam (International Journal of Economic Plants)
To reduce the existing yield gap of maize crop between research and farmer’s field, the experiment was carried out during the period from March, 2014 to June, 2014 at the experimental field of Sher-e-Bangla Agricultural University, Sher-e-Bangla Nagar, Dhaka, Bangladesh. The experiments were laid out in RCBD method with three replications and eight treatments including control viz. Treatment0=control (no fertilizer), Treatment1=recommended dose N250 P50 K100 S25 Zn2 B1 kg ha-1, Treatment2=American NPK+N250 P50 K100 S25 Zn2 B1, Treatment3=Bio-forge+N250 P50 K100 S25 Zn2 B1, Treatment4=Wuxal+N250 P50 K100 S25 Zn2 B1, Treatment5=Peak+N250P50K100S25Zn2B1, Treatment6=Root Feed+N250 P50 K100 S25 Zn2 B1 and Treatment7=Nitro Plus + N250 P50 K100 S25 Zn2 B1 and three maize varieties namely Variety1=BARI Hybrid Bhutta-5, Variety2=BARI Hybrid Bhutta-6 and Variety3=BARI Hybrid Bhutta-9. Growth and yield contributing characters mainly plant height, cob length, cob weight, 100-kernel weight and kernel yield of maize crop were significantly influenced by the next generation fertilizers. Bio-forge along with other recommended fertilizers performed the best compared to other treatments of the study in aspect of kernel yield (5.95 t ha1) and statistically similar result showed by Root Feed along with other recommended fertilizers and produced 5.12 t ha1 kernel yield.